Regulation and co-regulation of product placement for OTT SVODs: The case of Netflix. (1st September 2018) - Dagnino, Gloria
Commercial communications constitute one of the policy areas where differences between traditional broadcasting media and over-the-top (OTT) subscription video on-demand services (SVODs) emerge more dramatically. This article focuses on the exemplary case of global market leader Netflix to examine how this US-born company has been adjusting to EU regulation on product placement (PP) identification. Moreover, the article presents and discusses some of the criticisms that were raised with regard to Netflix's supposed violation of the ban on the placement of tobacco products. The article argues that Netflix still fails to adequately disclose PP to its viewers. The article also advances a proposal for co-regulation on these matters, in light of the upcoming revised version of the EU Audiovisual Media Services Directive (AVMSD). An effective regulation of PP in OTT SVOD programmes is essential because watching Internet-based television is ever more a mainstream habit, particularly among young demographics, and because PP is a key revenue source for ad-free services like Netflix.